The Rebirth of Uzbekistan - Vladimir Mesamed (International Institute of Islamic Thought, 2005)
It is very difficult to avoid the conclusion that instead of getting involved in the broader democratization process, the new post-Soviet states of Central Asia have resisted such trends. At present, many of them, including the Republic of Uzbekistan, are considered the most authoritarian states in the world. The Uzbek authorities’ savage and bloody suppression of a massive people’s protest on May 13, 2005, shocked the international community. After the Soviet Union’s disintegration, Uzbekistan became the only Central Asian state with a prepared long-term strategy of economic reform. However, the overwhelming incompetence of the Uzbek leadership and the prevalent corruption among Uzbek officials caused the Uzbek model of market economy, outlined by President Islam Karimov in the initial period of reform, to fail. At first glance, it might seem rather ostentatious to claim that this book is a first attempt to study systematically the political, economic, social, and cultural changes that have taken place in this country for the last decade. Indeed, since the Soviet Union’s collapse, hundreds of books and research articles on the current situation in the post-Soviet Muslim states have been published. However, as Bogdan Szajkowski’s “Foreword” suggests, the author conducted his research with an acute and critical eye for facts and details (p. ix), which makes this book the first truly comprehensive study of contemporary Uzbekistan. The first chapter looks at Central Asia’s history, the period prior to its annexation by the Russian Empire, and (very briefly) the decades of the late-nineteenth and early-twentieth century prior to the Bolsheviks’ takeover. The following chapters examine the main developments during the Soviet period and investigate the roots of Uzbekistan’s totalitarian regime. The author stresses that from the beginning, the Uzbek government ignored the idea of a pluralist democracy. For example, the first manifestations of an independent Uzbekistan, the student protests at the capital’s university in mid-January 1992 that, apparently, were triggered by the liberalizing spirit of the time and raised slogans of democratic political opposition, were brutally crushed. The Law on Political Parties, which came into force in December 1996, introduced a multi-party political system. At the same time, the Uzbek party system held the prospective parties in check. Yalcin writes that in the first stage of multi-partisanship (1991-93), Uzbekistan had three parties and one political movement. By late 1993, two of them, the Erk Democratic Party and the Birlik Movement, were banned and most of the opposition leaders were exiled (pp. 54-56). Some prominent opposition figures were imprisoned and some simply disappeared from the political scene. At present, with the exception of the People’s Democratic Party of Uzbekistan (PDPU) that is the successor of the Communist Party of Soviet ...